Novel Modeling Methodology for Thermal Evaluation of an Electrically Assisted High-Speed Turbomachine - Georgios S. Arvithis; Georgios Iosifidis; Roberto DeSantis; Martin Rode; Raphael Burgmair; Anestis I. Kalfas (Engineering Proceedings)
Hydrogen-based fuel-cell systems are a promising technology for reducing carbon footprint in the portfolio of future propulsion system concepts for small-range and regional aircraft In order to increase efficiency, the application of a turbo-charged air supply, using a compressor stage, a turbine stage, and an electric motor, has proven to be beneficial. This paper explores the thermal management aspects of a pioneering Electrified Turbo Charger designed for fuel-cell applications. A novel approach employing gas-cooling for the electric machine is investigated through simulation using an adiabatic Computational Fluid Dynamics (CFD) model. Bulk-flow-based Heat Transfer Coefficients (BHTCs) and temperatures are extracted from the CFD Analysis and serve as boundary conditions in a Solid Thermal model. Additionally, a 3D transient electromagnetic analysis is employed to assess losses in various components of the machine, which are then integrated into the 3D Solid Thermal Model. Initial evaluation of the temperature distribution is conducted, and subsequent analysis highlights uncertainties inherent in this methodology.